1999
DOI: 10.1039/a904504j
|View full text |Cite
|
Sign up to set email alerts
|

Subtle differences in molecular recognition between modified glycopeptide antibiotics and bacterial receptor peptides identified by electrospray ionization mass spectrometry

Abstract: In determining structure-activity relationships, it is advantageous if binding constants for a variety of ligands to a given target molecule can be directly obtained from a single aqueous solution containing a mixture of ligands and the target molecule. In this paper further evidence is provided showing that electrospray ionization mass spectrometry (ESI-MS) can be used in the rapid quantitative analysis of mixtures of vancomycin-group antibiotics and their bacterial cell-wall receptors allowing the identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…Speci®city and relative af®nities can be determined by a comparison of the relative intensities of ions that correspond to the complex and uncomplexed macromolecules. Caution must be exercised so that ions that arise from complexes of similar composition are compared, because these complexes will have comparable ionization ef®ciencies (Jorgensen et al, 1999).…”
mentioning
confidence: 99%
“…Speci®city and relative af®nities can be determined by a comparison of the relative intensities of ions that correspond to the complex and uncomplexed macromolecules. Caution must be exercised so that ions that arise from complexes of similar composition are compared, because these complexes will have comparable ionization ef®ciencies (Jorgensen et al, 1999).…”
mentioning
confidence: 99%
“…Second, competition experiments can be used to evaluate the stability of noncovalent complexes. In Jørgensen's method [23,24], the relative intensities of the free host and the different complexes were used, whereas Kempen et al employed the known concentration of a reference complex to determine the concentration of an unknown complex [25]. Third, a titration of a host with a guest (or vice versa) can be used.…”
mentioning
confidence: 99%
“…For instance, it has been reported that CDP-I has no antibacterial activity (30). Previously we have shown that electrospray ionization can be used quantitatively to determine solution-phase association constants between vancomycin group antibiotics and bacterial cell wall receptor analogues (3,25,26,33,34). The bioaffinity ESI-MS method relies on the assumption that the antibiotics and their noncovalent complexes with the receptor-mimicking peptides have relatively the same ionization efficiencies.…”
Section: Determination Of Association Constants Using Nanoelectrospramentioning
confidence: 99%